Pelatihan Mendeteksi FRAUD Pada Koperasi di Kabupaten Kudus - Dwi Soegiarto; Ulva Rizky Mulyani (Muria Jurnal Layanan Masyarakat, 2022)
Cooperative management requires an understanding of fraud in cooperatives. Understanding the potential for fraud is very important to be implemented in cooperatives. However, many cooperatives do not understand the fraud. The purpose of this service is to provide training for cooperative managers on the importance of identifying potential fraud, provide training for cooperative managers on how to prevent fraud that can be carried out by cooperative managers. The method used is a participatory method by conducting training for cooperative managers in Kudus Regency. The results obtained by the training participants were serious in accepting the material presented by the presenters and enthusiastic in participating in the training. This can be seen by the number of questions, responses received by the presenters and the discussions that occurred during the presentation of the material.